Um aluno-pesquisador na pandemia: o papel da pesquisa científica na formação acadêmica - Slywitch Filho, Glieb (Universidade Federal de São Carlos, 2023)
This undergraduate thesis is a critical-reflexive narrative in accordance with the guidelines of the Federal University of São Carlos’s medical school’s Pedagogical Project and aims to show the trajectory and experiences of a medical student during graduation. The narrative is organized in such a way as to expose, through the student's vision and experience, the development of an undergraduate research project, within the University Hospital, during the COVID-19 pandemic, in the year of 2020.
A student-researcher in the pandemic: the role of scientific research in academic education
Keywords: Medicina; Narrativa crítico-reflexiva; Iniciação científica; Pandemia; COVID-19; TCC; UFSCar; CIENCIAS DA SAUDE::MEDICINA; CIENCIAS HUMANAS::EDUCACAO